2013 IEEE Nuclear Science Symposium and Medical Imaging Conference (2013 NSS/MIC) 2013
DOI: 10.1109/nssmic.2013.6829281
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT image denoising and segmentation based on a multi observation and a multi scale Markov tree model

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Improving image quality, specifically through noise reduction, is a crucial step prior to performing CT image prediction. From the literature [19][20][21][22], it is confirmed that the noise in CT images is typically additive white Gaussian noise. We selected nonlocal mean filtering for denoising, as it searches for similar areas in the image in units of image blocks and then averages these areas, which can better filter out the Gaussian noise in the image.…”
Section: Image Processingmentioning
confidence: 99%
“…Improving image quality, specifically through noise reduction, is a crucial step prior to performing CT image prediction. From the literature [19][20][21][22], it is confirmed that the noise in CT images is typically additive white Gaussian noise. We selected nonlocal mean filtering for denoising, as it searches for similar areas in the image in units of image blocks and then averages these areas, which can better filter out the Gaussian noise in the image.…”
Section: Image Processingmentioning
confidence: 99%